2019
DOI: 10.1016/j.neuropharm.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic caffeine exposure during adolescence and subsequent acute caffeine challenge during adulthood on rat brain serotonergic systems

Abstract: Caffeine is the most commonly used drug in the world. However, animal studies suggest that chronic consumption of caffeine during adolescence can result in enhanced anxiety-like behavioral responses during adulthood. One mechanism through which chronic caffeine administration may influence subsequent anxietylike responses is through actions on brainstem serotonergic systems. In order to explore potential effects of chronic caffeine consumption on brainstem serotonergic systems, we evaluated the effects of a 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Besides, most studies in animal models focus on a particular period of caffeine exposure (e.g. adolescence 13,[69][70][71][72] or prenatal life 73,74 ), which is usually not paralleled by the pattern of exposure that occurs in humans. Here, we tested the hypothesis that lifetime caffeine exposure alters nicotine effects and increases its reward properties during adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, most studies in animal models focus on a particular period of caffeine exposure (e.g. adolescence 13,[69][70][71][72] or prenatal life 73,74 ), which is usually not paralleled by the pattern of exposure that occurs in humans. Here, we tested the hypothesis that lifetime caffeine exposure alters nicotine effects and increases its reward properties during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…14,80 Here, we failed to identify alterations in the expression of hippocampal 5-HT 1A , which suggests that this receptor, in the hippocampus, does not play a critical role in the anxiety-like behavior evoked by lifetime caffeine. Arnold and colleagues 71 showed that caffeine exposure during adolescence does not affect mRNA expression of htr1a, the serotonin 1a receptor gene, however, it downregulates mRNA expression of other proteins involved in serotonergic transmission in the dorsal raphe nucleus of rats. These results suggest that other receptors and brain regions relevant to serotonergic-mediated modulation of anxiety should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published methods were used for in situ hybridization histochemistry using oligonucleotide probes [ 37 , 13 . To detect htr1a mRNA, two synthetic anti-sense oligonucleotides, one 49-base oligonucleotide (5′-ACG AAG TTC CTA AGC TGG TGC CTG CTC CCT TCT TTT CCA CCT TCC TGA C-3′, Integrated DNA Technologies, Coralville, IA, USA) complementary to bases 810–858 of rat htr1a mRNA and one 47-base oligonucleotide (5′-GCC TCA CTG CCC CAT TAG TGC ACG GAG TCC CCA CCG CCC TGT TCT CA-3′, Integrated DNA Technologies) complementary to bases 923–969 of rat htr1a mRNA, were used [ 37 .…”
Section: Methodsmentioning
confidence: 99%
“…No. 28,304, Qiagen, Valencia, CA, USA), and used in an in situ hybridization histochemistry assay as described previously [ 15 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serotonergic neurons in the raphe nuclei are chemosensitive and contribute to the hypercapnic ventilatory response ( Hodges et al, 2008 ; Teran et al, 2014 ). Serotonin release is inhibited by adenosine agonists and enhanced by adenosine antagonists ( Feuerstein et al, 1988 ; Okada et al, 2001 ; Arnold et al, 2019 ). Similarly, the retrotrapezoid nucleus is chemosensitive and may contribute to the hypercapnic ventilatory response ( Guyenet et al, 2016 ).…”
Section: The Badmentioning
confidence: 99%